FEATURES OF GLYCOME OF STRUCTURAL COMPONENTS OF THE LUNGS OF FEMALE RATS OFFSPRING UNDER THE CONDITIONS OF THYROID DYSFUNCTION - Strus, Kh.I.; Pankevych, L.V.; Shepitko, K.V.; Chelpanova, I.V.; Yashchenko, A.M.; Lutsyk, A.D. (World of Medicine and Biology, 2023)
The study of the mechanism of the occurrence of thyroid pathology in patients with a pulmonological profile is poorly covered in the domestic literature. With the use of the lectin-peroxidase technique, the role of the glycome of the structural components of the lungs of the offspring of rats under conditions of thyroid dysfunction in the maternal organism was studied in the experiment. At long-term stages of development of the offspring of rats of the experimental group, the redistribution of receptors of lectins of various carbohydrate specificity used by us in the structural components of the bronchial tree, the air-blood barrier, and alveolar macrophages was declared. This can cause changes in their functional properties, slow down gas exchange processes, change immune properties, and be a trigger for starting pathological processes in the lungs.
Keywords: rats; lungs; experimental hyperthyroidism; glycopolymers; lectins